Integration study of high quality teaching resources in universities - Honglu Liu; Shugang Zhang; Xiaolan Guan (Journal of Industrial Engineering and Management (JIEM), 2012)
Purpose: The development level and quality of education depend on the merits and efficiency in the use of teaching resources, especially in the case of obvious contradiction between the demand and supply of teaching resources. So to integrate teaching resources, improve the efficiency in the use of high quality teaching resources, and take the road of content development to enhance the competitiveness of education has become very important and urgent. Design/methodology/approach: On the basis of analysis on the teaching resources of universities and the problems they faced, this paper introduced the basic concepts of cloud storage, and built the integration architecture of high quality teaching resources in universities based on the cloud storage. Findings and Originality/value: The HDFS-based cloud storage proposed in this paper is a dynamically adjustable and Internet-based storage solution, and the users can access storage targets using the network through a common and easy-to-use protocol and application programming interfaces. This new technology is useful for end users benefits. With the continuous development and improvement of cloud storage, it will necessarily result in more and more applications in the institutions of higher learning and education network. Originality/value: This paper introduced the cloud storage into the integration of high quality teaching resources in universities first and as a new form of service, it can be a good solution.
Keywords: 650; High quality teaching resources; Integration; Cloud storage; Information platform